Letter: vedolizumab drug levels in cord and maternal blood in women with inflammatory bowel disease—authors' reply. Issue 3 (11th July 2018) - Mahadevan, U.; Vermeire, S.; Lasch, K.; Abhyankar, B.; Bhayat, F.; Blake, A.; Dubinsky, M.
Abstract : Linked Content This article is linked to Mahadevan et al and Julsgaard et al papers. To view these articles visithttps://doi.org/10.1111/apt.13960 andhttps://doi.org/10.1111/apt.14837 .